2006
DOI: 10.1136/bjo.2006.106724
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cataract surgery in Pakistan: results from The Pakistan National Blindness and Visual Impairment Survey

Abstract: Aim: To evaluate the outcomes of cataract surgery in Pakistan. Methods: Cross-sectional, nationally representative sample of 16 507 adults (aged >30 years). Each underwent interview, logarithm of the minimum angle of resolution visual acuity (VA), autorefraction, examination of optic disc. Those with ,6/12 VA on presentation underwent best-corrected VA and dilated biomicroscopic ocular examination. Results: 1317 subjects (633 men) had undergone surgery in one or both eyes. Of the 1788 operated eyes, 1099 (61%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 22 publications
4
50
3
1
Order By: Relevance
“…Postoperative refractive error, presumably resulting from inaccurate IOL selection and aphakia, has been reported as a leading risk factor for poor postoperative vision in several studies from rural Asia. [16][17][18][19][20][21][22] The median value (C21.5 D) of the IOLs implanted in this study agrees surprisingly well with values in other areas of the world. A median IOL power of C21.6 D has been reported in Vietnam 29 and of C21.9 D in Kenya.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Postoperative refractive error, presumably resulting from inaccurate IOL selection and aphakia, has been reported as a leading risk factor for poor postoperative vision in several studies from rural Asia. [16][17][18][19][20][21][22] The median value (C21.5 D) of the IOLs implanted in this study agrees surprisingly well with values in other areas of the world. A median IOL power of C21.6 D has been reported in Vietnam 29 and of C21.9 D in Kenya.…”
Section: Discussionsupporting
confidence: 88%
“…6,11,12 Risk factors for deviation from desired emmetropia include older age, 2 clear corneal (as opposed to limbal) incisions, 2 and use of anterior chamber IOLs. 13 Some studies in the developing world 14,15 report acceptable accuracy in the prediction of postoperative refraction, even using average-power IOLs, 14,15 with 45% to 54% of patients having a postoperative refraction within G1.00 D. 14 However, postoperative refractive error has been implicated as one of the most significant risk factors for poor visual and functional outcomes after cataract surgery in many reports from rural Asia, including those from Bangladesh, 16 Pakistan, 17 China, 18 and India. [19][20][21][22] Few studies from rural Asia have reported in detail the distribution of refractive error after cataract surgery.…”
mentioning
confidence: 99%
“…3 Over half of blindness in adults (51.5%) is due to cataract 4 and although cataract surgical coverage is high (77.1%) 5 31% of eyes that had undergone cataract extraction within 3 years of the survey had a presenting VA of < 6/60. 6 Limited evidence is available within Pakistan regarding subjective visual perceptions. This article, using data collected during the national survey, aims to evaluate VF and vision related QOL in a representative sample of normal, visually impaired and pseudo/aphakic adults (≥30 years).…”
Section: Introductionmentioning
confidence: 99%
“…The national survey of blindness in Pakistan identified 1788 operated eyes, of which outcome was good in 30%, borderline in 36%, and poor in 34%. 6 Again, refractive error was the dominant cause of poor/ borderline outcome, followed by surgical complications and concomitant diseases.…”
Section: Discussionmentioning
confidence: 99%